Dirty‐Appearing White Matter in the Brain is Associated with Altered Cerebrospinal Fluid Pulsatility and Hypertension in Individuals without Neurologic Disease. Issue 1 (20th April 2015) - Beggs, Clive B.; Magnano, Christopher; Shepherd, Simon J.; Belov, Pavel; Ramasamy, Deepa P.; Hagemeier, Jesper; Zivadinov, Robert
ABSTRACT: BACKGROUND AND PURPOSE: Aging of the healthy brain is characterized by focal or nonfocal white matter (WM) signal abnormality (SA) changes, which are typically detected as leukoaraiosis (LA). Hypertension is a risk factor for WM lesion formation. This study investigated whether LA might be associated with increased cerebrospinal fluid (CSF) pulsatility linked to arterial hypertension. METHODS: A total of 101 individuals without neurologic diseases (53 females and 48 males) aged between 18 and 75 years underwent 3T brain MRI with cine phase contrast imaging for CSF flow estimation, after providing their informed consent. LA was defined as the presence of focal T2 WM SA changes and/or nonfocal uniform areas of signal increase termed dirty appearing white matter (DAWM). Relevant information relating to cardiovascular risk factors was also collected. RESULTS: When controlled for age and hypertension, significant partial correlations were observed between: DAWM volume and: net negative flow ( r = –.294, P = .014); net positive flow (NPF) ( r = .406, P = .001); and peak positive velocity ( r = .342, P = .004). Multiple linear regression analysis revealed DAWM volume to be significantly correlated with CSF NPF ( P = .019) and hypertension ( P = .007), whereas T2 WM SA volume was only significantly correlated with age ( P = .002). Combined DAWM and T2 WM SA volumes were significantly related with age ( P = .001) and CSF peak negative velocity ( P = .041). CONCLUSIONS: Rarefaction of WM leading to LA is a multifactorial process, in which formation of DAWM induced by hypertension and increased aqueductal CSF pulsatility, may play a contributory role. These two factors appear to act independently of each other in a process that is independent of age.